Specifics of the development of students’ creative abilities in the context of higher education - Leonidovna Sokolova, Natalia (2021)
This study examines the problems of the development of students’ creative abilities, their structure and specifics, similarities and differences from creativity. The aim of the research is theoretical and empirical consideration of the specifics of students’ creative abilities and their development. The problems of the essence of creative abilities, the role of their formation in the young age, specific methods and techniques are revealed. The research methodology and its algorithm were selected due to the purpose of the study. Experimental work included a complex psychological and pedagogical experiment, consisting of the indicative, formative and control stages. The study of students’ creative abilities was carried out on the basis of the Institute of Foreign Languages of the Federal State Autonomous Educational Institution of Higher Education “The Peoples’ Friendship University of Russia” (RUDN). An experimental and a control group were formed, each included 45 people, the sampling is valid for all significant characteristics. The results of the study allow us to conclude that the training forms are especially effective in the development of students’ creative abilities. The level of development of the teacher’s creative abilities is a significant factor in the formation of students’ creative abilities.